Teachers' Experiences in Teaching Reading Comprehension Using Word Walls in Middle Schools - Sulala, Warda Anis; Pranata, Sofyan Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores an English teacher's experience implementing a Word Wall strategy to improve reading comprehension in a secondary school in East Java, Indonesia. Vocabulary limitations were identified as a major barrier to student reading comprehension. The study employed a descriptive qualitative design with a narrative inquiry approach, allowing for in-depth exploration of the teacher's personal, professional, and reflective experiences. Data were collected through classroom observations, semi-structured interviews, and documentation, and then analyzed thematically. Findings indicate that the Word Wall was systematically integrated into three stages of reading instruction: pre-reading (introducing key vocabulary with visual cues), during reading (identifying vocabulary in context), and post-reading (discussing meaning and applying vocabulary in sentences). This strategy improved vocabulary retention, comprehension test scores, self-confidence, and students' self-regulated learning. Challenges faced included limited classroom space and time to update materials; these were addressed through vocabulary rotation and student engagement. This study confirms that the effectiveness of the Word Wall depends not only on its presence but also on its creative integration into reflective teaching practices